Protective effects of inhaled carbon monoxide in endotoxin-induced cholestasis is dependent on its kinetics - Vanova, K; Suk, J; Petr, T; Cerny, D; Slanar, O; Vreman, H J; Wong, R J; Zima, T; Vitek, L; Muchova, L (Biochimie, 2014)
Carbon monoxide (CO), a product of heme oxygenase (HMOX), has many beneficial biological functions and is a promising therapeutic agent for many pathological conditions. However, the kinetics of inhaled CO and its protective role in endotoxin-induced cholestasis is not fully known. Thus, our objective was to characterize the kinetics of inhaled CO and then investigate its use in early phase experimental endotoxin-induced cholestasis. Female Wistar rats were randomly divided into 4 groups: CON (control), LPS (lipopolysaccharide, 6 mg/kg), CO (250 ppm COx1h), and CO + LPS. Rats were sacrificed at 0-12 h after LPS administration. Tissues and blood were collected for liver injury markers and tissue CO distribution measurements. Livers were harvested for measurements of Hmox activity, Hmox1 mRNA expression, cytokines (IL10, IL6, TNF), and bile lipid and pigment transporters. Half-lives of CO in spleen, blood, heart, brain, kidney, liver, and lungs were 2.4 ± 1.5, 2.3 ± 0.8, 1.8 ± 1.6, 1.5 ± 1.2, 1.1 ± 1.1, 0.6 ± 0.3, 0.6 ± 0.2 h, respectively. CO treatment increased liver IL10 mRNA and decreased TNF expression 1 h after LPS treatment and prevented the down-regulation of bile acid and bilirubin hepatic transporters (Slc10a1, Abcb11, and Abcc2, p < 0.05), an effect closely related to the kinetics. The protective effect of CO against cholestatic liver injury persisted even 12 h after CO exposure, as shown by attenuation of serum cholestatic markers in CO-treated animals. CO exposure substantially attenuated endotoxin-induced cholestatic liver injury and was directly related to the kinetics of inhaled CO. This data underscores the importance of the kinetics of inhaled CO for the proper design of experimental and clinical studies of using CO as a treatment strategy.
Keywords: Half-Life; interleukin-6; TNF-alfa; Rats; Gene Expression; žlučové cesty; Heme Oxygenase (Decyclizing); hemová oxygenasa (decyklizující); potkani Wistar; játra; Endotoxin; Cholestasis; Tumor Necrosis Factor-alpha; Animals; exprese genu; poločas; Liver; zvířata; Carrier Proteins; oxid uhelnatý; Bile Ducts; Interleukin-10; Bile; Interleukin-6; Lipopolysaccharides; krysa rodu Rattus; Carbon Monoxide; cholestáza; messenger RNA; lipopolysacharidy; Rats, Wistar; žluč; ženské pohlaví; Heme oxygenase; Female; transportní proteiny; interleukin-10; Carbon monoxide; RNA, Messenger